Leisure and health: conjoined and contested concepts. Issue 3 (27th May 2021) - Peel, Nicole; Maxwell, Hazel; McGrath, Richard
ABSTRACT: This paper explores the various ideas, notions and conversations that underpin the leisure/health nexus and focuses on identifying the interrelatedness and synergies between these concepts. There are competing understandings of 'health' that underpin the domains of leisure. Within these disciplines there are contrasting discussions involving biological, economic, environmental, historical, medical, political, psychological and sociological ways of constructing meaning. These occur in the domains of bio-medical treatment and health promotion framed within embodiment and embodiment practice. The bio-medical domain frames 'health' as the prevention of disease/illness/injury and views 'leisure' as a tool through which to reduce risk. While 21st century health promotion posits 'health' more holistically, 'leisure' still often focuses on issues related to individual's physical 'health'. In reality leisure and health are complex concepts that exist within a system of ebbs and flows that impact each other in different ways depending on your point of view.